Pengembangan Media Marble Maze Untuk Melatih Kemampuan Problem Solving Anak Usia Dini - Rizka, Sitti Muliya; Nasir, Nasir; Arfah, Wahyuni; Nessa, Rahmatun; Suhartati, Suhartati (UIN Sultan Maulana Hasanudin Banten, 2025)
Development Of Marble Maze Media For Training Problem-Solving Skills In Early Childhood. This research aims to produce valid Marble Maze media to enhance problem-solving skills in early childhood, specifically for children aged 4-5 years. The study follows a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observations, interviews, literature reviews, and questionnaires. The results indicate that the Marble Maze media, which is effective for enhancing problem-solving skills, features labyrinth games with winding paths and sticker challenges. The feasibility of the Marble Maze media, based on validation results from media experts, received a score of 90%, categorizing it as